A Simple Planar Antenna for Sub-6 GHz Applications in 5G Mobile Terminals - Zhirong An; Mang He (Applied Computational Electromagnetics Society Journal (ACES), 2020)
A simple planar antenna for sub-6 GHz applications in 5G mobile terminals is presented. The proposed antenna is composed of one multi-branch driven strip and three parasitic grounded strips, featuring simple design without using three-dimensional structure and lumped elements. The |S11| ≤ -6dB impedance bandwidth of the antenna covers 700-960 MHz and 1600-5500 MHz bands with a compact size of 40×15×0.8 mm3, which makes it fulfill the requirements of sub-6 GHz applications in the 5G terminals. The prototype of the antenna is fabricated, and the design is well validated by experimental results.